KONSTRUKSI GENDER MELALUI ORNAMEN HIAS PADA SENJATA TRADISIONAL KHAS SUMBAWA BARAT - Rahmat, Mi'rajus Subyan; Muhammad Tomi; Bayu Aji Pamungkas (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research deals with how the construction of gender is realized through decorative ornaments carved on berang traditional weapons in the community of Rempe Village, Seteluk District, West Sumbawa Regency. Berang is a traditional weapon of the Samawa tribe (Sumbawa) in the form of a cutting weapon made by a panre (blacksmith). In general, the people of Sumbawa recognize two types of berang namely the salaki berang (male), and the swai berang (female). The use of the term berang as a relative (brother), as well as the differences in the ornamentation of the two types of berang, is the reason for this research. The problem of this research is dissected by using Roland Barthes' semiotic concept. The results of this study indicate that in general, gender construction does occur through berang. This gender construction produces "standard values" that tend to be masculine but quite dynamic and negotiative. Furthermore, gender construction is illustrated by the classification of the ornaments, both in terms of the type and number of ornaments carved. This gender construction occurs, is inherited and strengthened by existing institutions in Sumbawa society such as the family, West Sumbawa District Government, Tana Samawa Traditional Institution, Rempe Village Government, schools, and the Kokar Telu group itself also plays an essential role as a legitimacy tool. in gender construction through berang. Keywords: Gender Construction, Ornament, Berang